Plan de intervención y su aporte en el desarrollo de memorias visuales y auditivas a estudiantes de la escuela de educación general básica la Inmaculada cantón Montalvo Provincia los Ríos. - Aguayo Barahona, Fanny Silvia (2016)
This research seeks to contribute to the development of visual and auditory memories, taking the necessary methodologies, implementing activities to help combat this problem, which affects greatly the learning that students acquire daily, since it reflects demotivation and it makes teaching becomes routine, making classes do not have the respective acceptance. Over time the development of visual and auditory memories will evolve in teaching and learning, so it is important that teachers implement the use of the intervention plan within the school which promote cognitive development, skills and skills in students. It is imperative that teachers update their knowledge and motivation promotes the development of visual and auditory to help learners who have problems such memories. In Chapter One shows the subject of research, and as has been the problem in Europe, in Ecuador, in the province and most elemental as is occurring in the Educational Unit "The Immaculate". In chapter two or referential theoretical framework shown the hypothesis is determined. In Chapter Three it is analyze the results of research using the survey as a method to make this final project report possible. In chapter four the proposal to be applied is detailed.